Environmental economics research and China's green development strategy - Zhang, Youguo (Series on Chinese economics research - Vol. 19, 2019)
"This book discusses several important issues in the practice of China's green development. It analyzes the carbon mitigation, water conservation and environmental pollution from the perspectives of economic development, technological change, production and demand. The book uses various quantitative methods to reveal the pathways of China's green development. The methods include Log Mean Divisia Index, input-output analysis, structural decomposition analysis, data envelope analysis, econometric methods and computable general equilibrium model. The findings, discussions and policy implications of this book contribute to the theory and policy studies in China's green development"--